Comparison of two yeast invertase genes: conservation of the upstream regulatory region. - Sarokin, L (1985)
The yeast genome contains a dispersed family of invertase structural genes (SUC1-SUC5, SUC7). Five of these genes are located very close to telomeres and are flanked by large regions of homologous sequence; recombination between telomeres could account for the dispersal of these SUC genes to different chromosomes. The SUC2 locus, in contrast, is not near a telomere and does not share large regions of flanking homology with the other loci. We examine here the relationship between SUC2 and one of the telomeric genes, SUC7. Sequence comparison revealed homology extending from about position -624 to +1791, which is close to the end of the mRNA. The 5' noncoding sequence includes two highly conserved regions: the region between -140 and +1, which contains the TATA box and presumably other promoter elements, and a second region extending from -508 to -400, which corresponds to the upstream regulatory region.